DESAIN PRODUK MELALUI TAHAPAN PENGEMBANGAN PRODUK MARKETABLE (Arthavidya Jurnal Ilmiah Ekonomi, 2022)
Product Life Cycle or product life cycle is an important indicator for designing and developing products, but it is only used to see the ability of a product to compete in the market on a regular basis. So that in planning product design, it is necessary to use tools or use good methods in order to create products that are competitive and effective and efficient. The purpose of this discussion is expected to be able to contribute to academics and society in general, regarding systematic steps in product design and development activities. This research uses a qualitative descriptive method through a case study on a beverage product, with the focus of the research on the process of developing product design concepts. Sources of data obtained from the study of literacy and data collection using observation and documentation. In developing the product design, Memories coffee issued a coffee variant in 250 ml packaging. By using an attractive bottle design and still maintaining its quality, making memorable coffee just for you becomes one of the most popular coffee brands on the market